(untitled) (Medical Forum Monthly, 2024)
Objective: Heart failure (HF) is a chronic disease usually associated with psychological issues especially anxiety/depression despite of medical treatments. Aim of our research data study was the estimation of level of depression among admitted CHF patients in Nishtar Hospital and to find an association of various clinical parameters with depression Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Cardiology Department of Nishtar Medical College and Hospital Multan from March 2016 to August 2016 Materials and Methods: 400 patients with systolic HF were divide according to the NYHA heart failure classification system. The level of depression was assessed by using Beck’s Depression Inventory questionnaire. The patients with a previous history of major depressive disease, psychological diseases, or chronic other severe ailments were excluded. To assess the relationship between variables the chi square test was applied to data. Results: 76 patients in group B of depression were hypertensive and in group A of depression 85 were hypertensive with p=0.04 that is significant i.e. p<0.05. The high depression of group B was much more common in heart failure group B with 53 people having severe depression and 96 group A CHF patients had mild depression with p=0.05 that is statistically significant. Similarly, 94 mildly depressed people were in joint family system of group J and 56 severely depressed patients were in group S with p=0.03 that is highly significant. Conclusion: Depression is very common among CHF patients who are living alone or with spouse only. And severe depression level is more common than mild/moderate depression at higher NYHA classes of CHF.